2015
DOI: 10.5301/hipint.5000231
|View full text |Cite
|
Sign up to set email alerts
|

Survival, Clinical and Radiological Outcome of the Zweymüller SL/Bicon-Plus Total Hip Arthroplasty: A 15-Year Follow-up Study

Abstract: The "third generation" Zweymüller total hip arthroplasty consisting of the SL stem and the Bicon cup has good long term results in terms of survival, clinical and radiological outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 21 publications
(35 reference statements)
2
9
1
Order By: Relevance
“…Clinical evaluation (using the HHS and VAS for pain) showed that patients experienced substantial improvements in health, although not as good as afforded by their primary operations, in agreement with the data of others who have reported clinical outcomes following placement of the tapered rectangular femoral stem. 34,35…”
Section: Discussionmentioning
confidence: 99%
“…Clinical evaluation (using the HHS and VAS for pain) showed that patients experienced substantial improvements in health, although not as good as afforded by their primary operations, in agreement with the data of others who have reported clinical outcomes following placement of the tapered rectangular femoral stem. 34,35…”
Section: Discussionmentioning
confidence: 99%
“…A titanium biconical threaded cup is quick, reliable, and easy to implant and does not require cementation. 7 9 In cementless total hip prostheses, the uncemented cup appears to be the component associated with increased risk of revision, compared to the stem. 18,27 It is stated that the common cause, for this problem, is increased polyethylene (PE) wear resulting in loosening.…”
Section: Discussionmentioning
confidence: 99%
“…Of 101 patients available for radiographic follow-up, the rate of aseptic loosening was 1.0% (1/101). Ottink K. et al also performed survival analysis of 13 to 15 years of follow-up and found the probability of stem survival with revision for aseptic loosening was 0.99 at 10 years and 0.95 after 15 years [16].…”
Section: Discussionmentioning
confidence: 99%